Criminal Law Protection Mechanisms for Virtual Property in Online Games under a Dual-Dimension Framework of Data and Property - Jiaran Zhang (International Journal of Social Sciences and Public Administration, 2026)
The amount of money involved in online game platform digital assets is relatively large, but whether they should be regarded as electronic data or lawful property has not been clearly defined in Chinese enforcement practice. Two-level assessment will be used in this paper to show that there is a disagreement over whether data-related crimes fall under Articles 285-286 and whether asset-based crimes fall under Articles 264 and 266 of the Criminal Code . The Reference Standards for Sentences, Evidence and Valuation are unequal. According to the judgments from 2019 to 2023, Chinese courts have been inconsistent in applying charges. We have put forward a general penalty index (CLI) and a two-tier system according to the theory of imaginary concurrence, and have also called for statutory recognition of digital assets and standardisation of judicial application rules.